2020
DOI: 10.3390/molecules25173859
|View full text |Cite
|
Sign up to set email alerts
|

Concise Total Synthesis and Antifungal Activities of Fusaric Acid, a Natural Product

Abstract: The total synthesis of a natural product alkaloid fusaric acid (FA), which exhibits herbicide, fungicide, insecticide and even diverse notable pharmacological activities, was accomplished in four steps using commercially available materials. The synthesis, based on a unified and flexible strategy using 6-bromonicotinaldehyde as a common intermediate, is concise, convergent, practical and can be carried out on a two-gram scale. This approach could be readily applicable to the synthesis of its analogues. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
(21 reference statements)
0
3
0
1
Order By: Relevance
“…FA, which is known for its powerful phytotoxicity, can accelerate the development of symptoms, such as internerval necrosis and foliar desiccation . Studies have demonstrated that FA has many pharmacological activities; e.g., (i) it is used as an antihypertensive , and anticancer drug; (ii) it is used in the treatment of Parkinson’s disease; and (iii) it is an important insect phenoloxidase inhibitor and has a positive insecticidal effect. , In our previous study, FA was reported to demonstrate considerable antifungal effects after treating 14 pathogens with FA, such as Colletotrichum higginsianum (EC 50 = 31.7 μg/mL), Thanatephorus cucumeris (EC 50 = 22.4 μg/mL), and Colletotrichum gloeosporioides (EC 50 = 90.8 μg/mL) . Therefore, we postulate that FA and its derivatives have considerable potential for their development into new fungicides.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…FA, which is known for its powerful phytotoxicity, can accelerate the development of symptoms, such as internerval necrosis and foliar desiccation . Studies have demonstrated that FA has many pharmacological activities; e.g., (i) it is used as an antihypertensive , and anticancer drug; (ii) it is used in the treatment of Parkinson’s disease; and (iii) it is an important insect phenoloxidase inhibitor and has a positive insecticidal effect. , In our previous study, FA was reported to demonstrate considerable antifungal effects after treating 14 pathogens with FA, such as Colletotrichum higginsianum (EC 50 = 31.7 μg/mL), Thanatephorus cucumeris (EC 50 = 22.4 μg/mL), and Colletotrichum gloeosporioides (EC 50 = 90.8 μg/mL) . Therefore, we postulate that FA and its derivatives have considerable potential for their development into new fungicides.…”
Section: Introductionmentioning
confidence: 93%
“…29,30 In our previous study, FA was reported to demonstrate considerable antifungal effects after treating 14 pathogens with FA, such as Colletotrichum higginsianum (EC 50 = 31.7 μg/mL), Thanatephorus cucumeris (EC 50 = 22.4 μg/mL), and Colletotrichum gloeosporioides (EC 50 = 90.8 μg/mL). 31 Therefore, we postulate that FA and its derivatives have considerable potential for their development into new fungicides.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Ein Effekt, der auch für die Droge beschrieben ist [12]. Darüber hinaus besitzt Fusarinsäure antivirale, antifungale sowie antiproliferative Effekte [21].…”
Section: Anmerkung Zum Gegenwärtigen Wissensstandunclassified
“…Fusaric acid (FA), 5-butylpicolinic acid, is a mycotoxin that has been isolated from certain species of Fusarium and is a kind of Fusarium natural fungal metabolite ( Bacon et al, 1995 ; Thanh et al, 2020 ). Studies have shown that FA has good antibacterial effects ( Huang et al, 2020 ). However, the antibacterial effect and molecular mechanism of FA against S. haemolyticus are still unclear.…”
Section: Introductionmentioning
confidence: 99%